1977
DOI: 10.1113/jphysiol.1977.sp011770
|View full text |Cite
|
Sign up to set email alerts
|

Metiamide and stimulated acid secretion from the isolated non‐distended and distended mouse stomach.

Abstract: 1. The action of metiamide, a specific histamine H2-receptor antagonist, on the acid secretary response to various gastric stimuli in the perfused isolated whole mouse stomach is described. 2. Two kinds of stomach preparations, the non-distended stomach and distended stomach, were used. The distended stomach gave a marked and dose-related acid secretary response to histamine (10-6 to 10-3 M), pentagastrin (10-8 to 10-5 M), acetylcholine (5 x 10-5 to 10-5 M), eserine (10-5 to 10-3 M) or dibutyryl cyclic AMP (5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
1

Year Published

1980
1980
1993
1993

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 29 publications
4
19
0
1
Order By: Relevance
“…Davenport & Chaure (1950) tried to improve delivery using hyperbaric oxygen. Wan (1977) found that mouse stomachs would only secrete when distended. All the preparations which secrete well, in vitro, have thin walls -immature rat stomachs, mature mouse stomachs, guinea-pig mucosal sheets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Davenport & Chaure (1950) tried to improve delivery using hyperbaric oxygen. Wan (1977) found that mouse stomachs would only secrete when distended. All the preparations which secrete well, in vitro, have thin walls -immature rat stomachs, mature mouse stomachs, guinea-pig mucosal sheets.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the last few years or so, it has become possible to measure the secretion of acid by the intact stomachs of mature mice (Wan, 1977;Angus & Black, 1978); by the intact stomachs of immature guinea-pigs (Spencer, 1974) and rats (Parsons, 1975); by the mucous membrane, separated as a sheet, from kittens (Tepperman et al, 1975) and piglets (Forte et al, 1975); and by mixed but enriched suspensions of separated oxyntic cells (Soil, 1977). In addition, some of the biochemical elements subserving acid secretion, such as the hormone-receptor coupled systems on the basal membranes (Scholes et al, 1976) and the H+/ K+-ATPase located on the apical membranes (Fellenius et al, 1981) are now available for pharmacological studies.…”
Section: Introductionmentioning
confidence: 99%
“…The isolated, lumen-perfused stomach of the mouse is now a standard preparation for studying the pharmacology of oxyntic cell secretion (Wan, 1977;Angus & Black, 1979;Szelenyi & Vergin, 1980;Mahklouf & Schubert, 1990). Under basal conditions, this preparation lowers the pH of the unbuffered perfusate from about 6.0 to about 4.4.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of atropine and secoverine on bethanechol-induced gastric acid secretion and bethanechol-induced motility were investigated in vitro, using stomachs, removed from adult ASH/TO albino mice of either sex, weighing between 15 to 25 g. The technique was based on that described by Bunce &Parsons, (1976) andWan, (1977). All experiments were carried out on stomachs from two mice, one to measure secretion and the other motility.…”
Section: Introduction Methodsmentioning
confidence: 99%